2018
DOI: 10.3390/nu10091217
|View full text |Cite
|
Sign up to set email alerts
|

Do Aspects of Protein Intake Vary Across the Week in Healthy Community-Dwelling Older Adults?—An enable Study

Abstract: Various aspects of protein intake are thought to be crucial for the prevention of sarcopenia in older adults. Information about the day-to-day variation in these aspects is lacking. Our objective was to examine whether daily protein intake, protein distribution across meals, number of meals providing adequate protein, and protein sources vary across the week in healthy community-dwelling older adults. In 140 persons (51% women) that were aged 75–85 years, protein intake was assessed by seven-day food records. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 37 publications
1
6
3
Order By: Relevance
“…This is low compared to previous findings in community-dwelling adults 75-85 years where a weekly range between 30 and 60% was shown (17). However, participants with recent weight loss, very low or high BMI or several chronic conditions, including diabetes, lung diseases and heart conditions were excluded in the latter study (17). Hence, the greater proportion of meals with minimum protein content of 0.4 g/kg may reflect a more selected group of community-dwelling older adults (17).…”
Section: Dietary Patterns and Association With Protein Intakecontrasting
confidence: 95%
See 4 more Smart Citations
“…This is low compared to previous findings in community-dwelling adults 75-85 years where a weekly range between 30 and 60% was shown (17). However, participants with recent weight loss, very low or high BMI or several chronic conditions, including diabetes, lung diseases and heart conditions were excluded in the latter study (17). Hence, the greater proportion of meals with minimum protein content of 0.4 g/kg may reflect a more selected group of community-dwelling older adults (17).…”
Section: Dietary Patterns and Association With Protein Intakecontrasting
confidence: 95%
“…Day-to-day variability in protein intake has previously been reported in community-dwelling older adults (17). The present study found that day-to-day and meal-to-meal variability in protein intake was significantly greater in the low protein group (Table 2) and that a high day-to-day variability (operationalized as >20%) was associated with higher odds of low protein intake ( Table 3).…”
Section: Dietary Patterns and Association With Protein Intakesupporting
confidence: 76%
See 3 more Smart Citations